2017
DOI: 10.3390/land6010014
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Islandscapes: Conceptual and Methodological Challenges Exemplified in the Mediterranean

Abstract: Abstract:Islands across the world have evolved at the interface between land and sea, thus comprising landscapes and seascapes. Many islands have also been influenced by anthropogenic factors, which have given rise to mosaics of anthromes (sensu Ellis and Ramankutty). These elements of landscapes, seascapes, and cultural impacts in varied proportions, generate unique environments which merit a unique term: islandscapes. The use of the term islandscape is advocated as the only term which encompasses all of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…For example, the extensive coastline is usually neglected in many regional and national land based typologies. This has led to the development of Seascapes Assessment and a call for treating islands as separate entities [28]. Rangelands are important elements of the landscapes, culturally and economically, in the Mediterranean and the study areas examined are no exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the extensive coastline is usually neglected in many regional and national land based typologies. This has led to the development of Seascapes Assessment and a call for treating islands as separate entities [28]. Rangelands are important elements of the landscapes, culturally and economically, in the Mediterranean and the study areas examined are no exception.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pace of landscape characterization and mapping has been slower in the Mediterranean compared to Northern Europe there has been significant progress in recent years [20,28]). A comparison with the existing typologies which account for Mediterranean landscapes [15,21] revealed that the first study identified 7 landscape types in the whole Mediterranean Basin while the second 11 landscape types at the 3rd level of classification.…”
Section: Discussionmentioning
confidence: 99%
“…A natureza de uma ilha reflete um certo grau de isolamento, e isso pode constituir uma desvantagem (WHITTAKER; FERNANDEZ-PALACIOS, 2007), já que sua porção terrestre pode não oferecer suficiente apoio para comunidades humanas, sem que estas necessitem recorrer aos recursos costeiros ou marinhos. Nesse sentido, a insularidade exerce influência sobre as atividades humanas e pode gerar "dependência" física (VOGIATZAKIS; ZOMENI; MANNION, 2007).…”
Section: N T R O D U ç ã Ounclassified
“…To understand Malta as the nodal point of the local, national and the global without falling into the trap of 'islandism', we develop the concept of islandscape (Broodbank, 2000, p.21) for inductive, empirical research on, about and with islands as a further contribution to the debate on relationality within Island Studies. This concept has already received broad attention in geography (Arnaud, 2008), environmental studies (Vogiatzakis, Zomeni & Mannion, 2017), as well as archaeology (Bright, 2011;Frieman, 2008). According to Broodbank (2000), islandscape understands the island with its connections to other islands, to the (EUropean) mainland as well as to and with the sea, and is therefore a much more flexible concept compared to insularity, speaking to concepts like the aquapelago (Hayward, 2012) or approaches as thinking with the archipelago (Pugh, 2016).…”
Section: Islandscape As An Analytical Toolmentioning
confidence: 99%